지하철 터널 미세먼지 제거용 1단 전기집진기의 성능특성 - 김민락; 배귀남; 우상희; 김종범 (한국냄새환경학회, 2016)
A single-stage electrostatic precipitator (ESP) was evaluated in terms of its performance in removing dust insubway tunnels. A wire-to-plate type ESP was tested in a small-scale wind tunnel. The effects of wire-to-wirespacing (2040mm) and the material connecting wire-to-wire on the performance of ESP were investigated, withvarying applied voltage and airflow velocity. A narrower wire-to-wire spacing showed higher collection efficiencyat the same applied voltage. Lower electrical resistivity of material connecting wire to wire was more effective. Ozone generation in subway tunnel applications was insignificant.